Analysis of attacking episodes in soccer - Siegle, M.; Siles, F.; Beetz, M.; Lames, M. (Sportinformatik trifft Sporttechnologie. Tagung der dvs-Sektion Sportinformatik und der deutschen interdisziplinären Vereinigung für Sporttechnologie vom 15.-17. September in Darmstadt. Abstracts, 2011)
Using computer vision and image processing techniques, the DFG-project ASpoGAMo produces positional data from soccer players, referees and the ball (Beetz, et al., 2005 & 2009). Finding useful and important ways to use these data is province to sports science. One of these ways is to analyze ball possessions of teams, so called "episodes", in order to gain information about different tactics and the character of the game.